Context, Community, and Capital - Susanne Schindler (Footprint)
This essay focuses on the language architects use to navigate the intersection of architecture, housing, and neoliberalism. Schindler argues that terminology plays a powerful role in allowing architects to avoid the socio-economic assumptions embedded in their work. Schindler traces the emergence, evolution, and codification of two such terms, ‘context’ and ‘community’, and how they have frequently been conflated. She shows how they were central to New York City’s gradual shift from welfare-state to neoliberal housing policies between the mid-1960s and the present day by connecting them to a third key term, ‘capital’. The vest-pocket housing plan developed for the South Bronx as part of the federal Model Cities programme serves as a case study. In the Bronx, the triangulation of community, context, and capital led to new development models, as well as new housing typologies, including the large-scale rehabilitation of existing tenements and small-scale new construction of row houses. The resulting shift in architectural discourse, and the codification of these practices in zoning and tax laws, have remained in force in New York City to this day.